Manajemen Inovasi Digital dan Etika Organisasi dalam Penguatan Transparansi dan Akuntabilitas Pemerintahan Indonesia - Widaningsih; Susi Adiawaty (Journal of Citizenship, 2026)
This article examines the role of digital innovation management and organizational ethics in strengthening transparency and accountability in Indonesian government institutions. The article is grounded in the argument that digital transformation in the public sector should not be understood merely as technological modernization, but as an organizational management process involving leadership, institutional capacity, coordination, control systems, and public value orientation. This study uses a qualitative approach with a narrative literature review design based on journal articles, books, regulations, official government documents, and reports from international institutions relevant to digital government, public sector management, organizational integrity, and accountability. The findings show that electronic-based government systems, e-procurement, open data, online complaint platforms, and data-driven auditing can improve managerial effectiveness through stronger traceability, wider access to information, and better institutional control. However, the effectiveness of these instruments depends on organizational capacity, managerial commitment, data governance quality, interoperability, internal control mechanisms, and digital inclusion. The article concludes that successful digital transformation in Indonesian government requires the integration of digital innovation management, organizational ethics, and institutional control in order to produce not only procedural transparency but also substantive accountability and improved governance performance. Keywords: digital innovation management; organizational ethics; transparency; accountability; public sector management